On the macroscopic parameters of brittle fracture - Morozov, N.F.; Petrov, Y.V. (Archives of Mechanics, 1996)
The problem of modeling of some of the specific effects of brittle fracture in the high loading rate conditions is discussed. An approach based on the system of fixed material constants describing macro-strength properties of the material is considered. New principles of material testing are analyzed. The corresponding incubation time criterion allows us to manage without the a priori given rate dependences of dynamic strength and fracture toughness. New applications of the criterion to the problems of disintegration and erosion are considered.